Sectorial shifts and inequality: How to relate macroeconomic events to inequality changes - Carlos Villalobos Barría (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2012)
This paper presents a way to explore how macroeconomic shifts cause inequality changes. It is based on the backwardness observed in the agricultural sector in rural areas. It shows why highly dualistic economies tend to be more unequal than economies with flexible and integrated labour markets. Assuming that an inter-sectorial wage gap exists, this methodology allows control over the direct impact on inequality changes caused by macroeconomic changes that affects the relative competitiveness between the tradable and non-tradable sectors. The methodology aims to find the wage gap change (in log units) taking place between two points in time, which is not dependent on the distribution of endowments of the employed population (observed and unobserved characteristics). The decomposition methodology here proposed shows to be consistent under few assumptions (log normal distribution of earnings and inter-sectorial stochastic dominance) and was tested using real and simulated data. The procedure supports the conclusions by Devillanova et al. (2010) suggesting a channel through which trade integration can affect the wage inequality in a context of capital-skill complementarity and imperfect mobility of workers. The main conclusion of this paper is that duality is a source of inequality. Therefore, policies oriented to eliminate the systematic backwardness appear to be highly desirable in such economies.
Keywords: D63; C15; 330; Inequality; Decomposition; Wage-gap; Tradable and Non-tradable sectors; Micro-econometric Simulations; Lohnstruktur; Einkommensverteilung; Strukturwandel; Handelbare Güter; Nicht-handelbare Güter; Dualökonomie; Dekompositionsverfahren; Theorie; Simulation